Analysis of Wastewater Treatment Performance in Animal Slaughtering Industry: Evaluation of Efficiency and Wastewater Quality - Iva Rustanti Eri Wardoyo; Ferdiansah Ananda Putra; Marlik Marlik; Ferry Kriswandana; Elmi Sumiyarsono (Postgraduate, University of Mataram, 2025)
The slaughterhouse industry generates liquid waste with high organic loads and complex composition, which can pose environmental and public health risks. This study aims to evaluate the performance of a liquid waste treatment plant in a slaughterhouse. Quantitative methods were used for objective measurements, with sampling conducted at five key points in the wastewater treatment system. Parameters analyzed included pH, DO, COD, TSS, NH3, and fat, oil, and grease. The results showed that The Collecting Tank exhibited high COD reduction efficiencies between 87.52% and 93.89%, alongside TSS reductions ranging from 83.15% to 92.95%. Conversely, the Sequencing Batch Reactor demonstrated inefficiency in COD reduction, with outlet measurements exceeding inlet values; however, it achieved a 50.44% reduction in NH3 in one instance. The Anaerobic Tank showed significant COD reduction efficiencies from 72.66% to 98.27%, but NH3 reduction was negligible. Lastly, the Secondary Clarifier was inefficient in COD performance, with all tests indicating higher outlet results, while TSS efficiency was noted in only one test at 71.96%. The conclusion was although the Collecting Tank and Anaerobic Tank showed high efficiency in COD reduction, the Sequencing Batch Reactor and Secondary Clarifier units showed the NH3 reduction efficiency varied among the units tested.